Demographic, residential, and socioeconomic effects on the distribution of 19th century US white statures - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2009)
Using a source of 19th century US state prison records, this study addresses European-American stature variation. The most commonly cited sources for stature variation are diets, disease, and work effort. However, vitamin D is also vital in human statures and health. This paper demonstrates that 19th century white statures were positively associated with direct sunlight, which is the primary source of vitamin D in mammals. Stature and insolation are associated with occupations, and workers who spent more time outdoors produced more vitamin D and grew taller. White statures also decreased throughout the 19th century, and this stature diminution is observed across the stature distribution.
Keywords: I30; I31; J00; J15; 330; 19th US white statures; vitamin D; solar radiation; quantile regression; Lebensstandard; Farbige Bevölkerung; Weiße; Klima; Soziale Ungleichheit; USA